Diversity of Anammox Bacteria from Landfill Treatment Plant Sludge in Tropical Area - Zulkarnaini, Zulkarnaini; Atsil, Nadiah; Aribah, Hillary Citra; Komala, Puti Sri; Silvia, Shinta; Matsuura, Norihisa (Applied Science and Engineering Progress, 2024)
The anaerobic ammonium oxidation (anammox) process is known as the warm process. Tropical areas have an advantage due to their consistent temperature throughout the year. This study analyzed the diversity of anammox bacteria in the tropical area using leachate sludge from a landfill as an inoculum in a filter bioreactor (FtBR) and observed nitrogen removal performance. Ammonium and nitrite concentrations of 70, 150, and 200 mg-N/L were delivered into the reactor continuously with hydraulic retention time (HRT) of 24 h and 12 h and run for 131 days at ambient tropical temperature (25–28 °C). High performance achieved with nitrogen removal rate (NRR), nitrogen removal efficiency (NRE), and ammonium conversion efficiency (ACE) were 0.866 kg-N/m3.d, 99.19%, and 98.90%, respectively. The cultivated leachate sludge could perform an anammox process with four anammox species, Candidatus Brocadia fulgida, Candidatus Brocadia sapporoensis, Candidatus Brocadia sp uncultured, Candidatus Jettenia sp with abundance 6.52%, 13.82%, 0.77%, and 0.69%, respectively. These findings contribute to the advancement of biotechnology in wastewater treatment, particularly in tropical countries, and highlight the potential for highly cost-effective technology.